Demonstration of high-brightness-mode propagation in a compound waveguide structure - HEGARTY, JOHN (American Institute of Physics, 1999)
We demonstrate the existence of an unusual and useful high-brightness guided mode of a multimode AlGaAs/GaAs heterostructure compound slab waveguide. This mode has a narrow near-field single lobe confined to the low-index regions of the waveguide. This mode was selectively probed by optically exciting quantum wells optimally placed in the waveguide. By pumping in a stripe geometry, lasing is observed above a threshold of 80 kW/cm2 indicating efficient lasing in the highest-order waveguide mode. The near-field emission pattern of the waveguide was imaged to provide a direct measurement of the intensity profile of the higher-order mode.
PUBLISHED
Keywords: Physics